Long Non-coding RNA SNHG12, a New Therapeutic Target, Regulates miR-199a-5p/Klotho to Promote the Growth and Metastasis of Intrahepatic Cholangiocarcinoma Cells - Yang, Hong-Guo; Wang, Tian-peng; Hu, Sheng-an; Hu, Chao-zhou; Jiang, Cheng-hang; He, Qiang (Frontiers in Medicine, 2021)
Background: Small nucleolar host gene 12 (SNHG12) is a newly identified long non-coding RNA (lncRNA) whose involvements have been explored in several cancers. Our study aimed to explore the functions of SNHG12 on intrahepatic cholangiocarcinoma (ICC) progression and its interaction with miR-199a-5p and Klotho. Methods: RT-PCR was performed to examine the expressions of SNHG12, miR-199a-5p and Klotho in ICC cells. Cell counting kit-8 (CCK-8), colony formation assays and transwell assays were applied to analyze the proliferation, migration and invasion of ICC cells. Luciferase assays, RIP assays and RNA pull-down assays were carried out to demonstrate the direct binding relationships among SNHG12, miR-199a-5p and Klotho. The xenograft nude models were applied to test the effects of SNHG12 on ICC tumor growth. Results: The expression of SNHG12 and Klotho was distinctly increased in ICC cells, while miR-199a-5p expressions were decreased. Functionally, the silence of SNHG12 inhibited the proliferation and metastasis of ICC cells, while miR-199a-5p overexpression exhibited an opposite result. Mechanistically, Knockdown of SNHG12 significantly suppressed the expressions of miR-199a-5p by sponging it, and then increased Klotho expression. The final in vivo experiments suggested that the silence of SNHG12 distinctly inhibited tumor growth. Conclusion: Our findings indicated that SNHG12 inhibited cell proliferation and metastasis process of ICC cells through modulating the miR-199a-5p/Klotho axis and it is expected to become a potential therapeutic target for ICC.